Material identification and heavy metal characteristics of plastic packaging bags used in Chinese express delivery - Jiang, Yinhua; Song, Guanghan; Zhang, Hui (Frontiers in Environmental Science, 2023)
With the rapid development of China’s express delivery services, environmental concerns have increased owing to the use of plastic packaging bags (PPBs) which have a heavy metal (HM) content due to the incorporation of scrap plastics in the production process. We sourced a variety of PPBs from different express delivery parcels, identified the materials in the samples using Fourier-transform infrared spectrometry, and conducted HM analysis using inductively coupled plasma mass spectrometry. The results demonstrated that the main material type in the PPBs was polyethylene. The results showed that the potential health concerns were posed by the four HMs (nickel [Ni], copper [Cu], zinc [Zn], and arsenic [As]) presented in the PPB samples. The mean concentrations of HMs in the PPBs were ranked as follows (presented in unit mg kg−1): Zn (120.42 ± 85.15)> Cu (45.21 ± 56.55) > lead [Pb] (6.43 ± 6.57) > Cr (6.03 ± 6.82) > Ni (2.13 ± 2.14) > As (0.19 ± 0.15) > mercury [Hg] (0.17 ± 0.71) > cadmium [Cd] (0.14 ± 0.20). HM content varied according to sample type, with a ranking order of Rm > Pm > Bm, corresponding to the degree of environmental and health risk. For Rm samples, high levels of low-toxicity HMs, such as Zn and Cu were detected, with respective maximum values of 365.9 and 184.2 mg kg−1; furthermore, the levels of high-toxicity HMs (i.e., Cd and Hg) exceeded the standard values set by the express delivery sector (0.5 mg kg−1). Thus, more attention should be paid to the effective management of PPBs for polyethylene-based Rm types, such as the limitation of Zn, Cu, Cd, and Hg. This study provides baseline data regarding HM-incorporating PPBs for stakeholders and is expected to support the formulation of relevant products for use in greener packaging policy and, thus, contributes to the re-assessment of China’s “plastic ban” policy.